Severe aplastic anemia patients with infection who received an allogeneic hematopoietic stem cell transplantation had a better chance: Long-term outcomes of a multicenter study - Liu, Limin; Miao, Miao; He, Hailong; Wang, Shunqing; Zhang, Yanming; Guo, Ailian; Jiao, Wenjing; Lei, Meiqing; Cai, Yifeng; Shangguan, Xiaohui; Liu, Zefa; Xu, Jinge; et al. (Frontiers in Immunology, 2022)
Background and Aims: How to select the treatment is a challenge for the management of 34 acquired severe aplastic anemia (SAA) patients with infections. This study aimed at comparing the 35 outcomes of SAA with infections who had an allogeneic hematopoietic stem cell transplantation 36 (allo-HSCT)with that of patients who had an infection and received non-HSCT therapy. 37 Methods: We retrospectively compared the outcomes of patients with acquired severe aplastic 38 anemia (SAA) and infections who had an allo-HSCT (n = 141) with that of patients who had an 39 infection and received non-HSCT therapy (n = 186) between July 2004 and January 2020. 40 Results: The treatment-related mortality (TRM) of grade 1-2 infections in the HSCT and non- 41 HSCT groups was 24.99% and 13.68%, respectively (P = 0.206), while the TRM of grade 3-4 42 infections was lower in the HSCT group than that observed in the non-HSCT group (18.54% vs. 43 33.33%, P = 0.036). At 6 months post-treatment, 91.30% patients in the HSCT group and 8.78% 44 patients in the non-HSCT group had achieved a normal blood profile (P < 0.0001). The time required 45 to discontinue transfusions of red blood cells and platelets in the non-HSCT group was longer than in 46 the HSCT group (P < 0.0001). Estimated overall survival (OS) at 6 years was similar in the two 47 groups (75.5% ± 3.9% vs. 76.3% ± 3.1%, P = 0.996), while the estimated failure-free survival (FFS) 48 at 6 years was 75.2% ± 3.8% in the HSCT group and 48.9% ± 3.7% in the non-HSCT group (P < 49 0.0001). Multivariate analysis showed that younger age, lower grade of infection (grade 1-2), and 50 SAA (vs. very SAA) were favorable factors for OS (P < 0.05), and that the choice of HSCT and 51 younger age were favorable factors for FFS (P < 0.0001). 52 Conclusion: These results suggest that allo-HSCT has a better chance of a successful outcome 53 than non-HSCT in SAA patients with an infection.